BAP1 maintains HIF-dependent interferon beta induction to suppress tumor growth in clear cell renal cell carcinoma. (28th October 2022) - Langbein, Lauren E.; El Hajjar, Rayan; He, Shen; Sementino, Eleonora; Zhong, Zhijiu; Jiang, Wei; Leiby, Benjamin E.; Li, Li; Uzzo, Robert G.; Testa, Joseph R.; Yang, Haifeng
Abstract: BRCA1-associated protein 1 (BAP1) is a deubiquitinase that is mutated in 10–15% of clear cell renal cell carcinomas (ccRCC). Despite the association between BAP1 loss and poor clinical outcome, the critical tumor suppressor function(s) of BAP1 in ccRCC remains unclear. Previously, we found that hypoxia-inducible factor 2α (HIF2α) and BAP1 activate interferon-stimulated gene factor 3 (ISGF3), a transcription factor activated by type I interferons and a tumor suppressor in ccRCC xenograft models. Here, we aimed to determine the mechanism(s) through which HIF and BAP1 regulate ISGF3. We found that in ccRCC cells, loss of the von Hippel-Lindau tumor suppressor (VHL) activated interferon beta (IFN-β) expression in a HIF2α-dependent manner. IFN-β was required for ISGF3 activation and suppressed the growth of Ren-02 tumors in xenografts. BAP1 enhanced the expression of IFN-β and stimulator of interferon genes (STING), both of which activate ISGF3. Both ISGF3 overexpression and STING agonist treatment increased ISGF3 activity and suppressed BAP1-deficient tumor growth in Ren-02 xenografts. Our results indicate that BAP1 loss reduces type I interferon signaling, and reactivating this pathway may be a novel therapeutic strategy for treating ccRCC. Graphical abstract: Image 1 Highlights: Loss of VHL and activation of HIF2α increase interferon beta (IFN-β) levels. IFN-β is required for ISGF3 activation and suppresses tumor growth in xenografts. BAP1 enhances the expression of IFN-β and STING, activators of ISGF3. Genetic ISGF3 activation suppresses the growth of BAP1-deficient tumors. STING agonist activates ISGF3 and hinders the growth of BAP1-deficient tumors.